Outcome of AML patients with IDH2 mutations in real world before the era of IDH2 inhibitors. (June 2019) - Largeaud, Laetitia; Bérard, Emilie; Bertoli, Sarah; Dufrechou, Stéphanie; Prade, Naïs; Gadaud, Noémie; Tavitian, Suzanne; Bories, Pierre; Luquet, Isabelle; Sarry, Audrey; De Mas, Véronique; Huguet, Françoise; et al.
Highlights: Outcome of AML patients with IDH2 R172 mutations is favorable with a median OS of 41 months. Half of R/R AML patients with IDH2 mutations can achieve CR with conventional treatments. Median OS of refractory or first-relapsed IDH2mut AML patients is 15 months. Abstract: Describing the prognosis of sub-groups of acute myeloid leukemia (AML) patients treated in real world with current therapies is becoming increasingly relevant to estimate the benefit that new targeted drugs will bring in the field. This is particularly the case when novel drugs are registered on the basis of non-randomized studies. IDH2 inhibitors have recently emerged as promising drugs in patients with IDH2 R140 or IDH2 R172 mutations. Enasidenib, a first-in-class IDH2 inhibitor, has been approved following promising results of a phase 1–2 clinical trial in relapsed or refractory AML patients with IDH2 mutations. In this study, we described the characteristics, treatments and outcome of 75 IDH2 mutated patients both at diagnosis and relapse or refractory disease. Among the 33 relapsed/refractory AML patients with either IDH2 R140 or IDH2 R172, 28 (84.8%) patients received salvage therapy and 14 achieved a complete response (50%). Median duration of response was 15.2 months. Median, 1-y, 3-y and 5-y OS were 15.1 months (IQR, 4.6–37.7), 53.1% (95% CI, 33.2–69.5), 29.2% (95% CI, 12.6–48.1) and 24.4% (95% CI, 9.3–43.1), respectively. In responding patients, median OS was 37.7 months and 1-y, 3-y and 5-y OS was 85.7%, 57.1% and 47.6%, respectively. In non-responding patients, median OS was 5.0 months (IQR, 4.5–8.6) and 1-y and 3-y OS was 17.9% and 0%, respectively. Thus, a substantial number of R/R AML patients with IDH2 mutations can be salvaged by current treatments and benefit from prolonged survival. It is expected that novel targeted agents such as enasidenib will further improve efficacy and safety in the next future.